WTO and regional trade negotiation outcomes : quantitative assessments of potential implications on Bangladesh - Raihan, Selim; Razzaq, Abdur (Pathak Shamabesh, 2007)
On foreign commercial policy of Bangladesh in light of WTO and international trade practices.